THE IMPACT OF THE MODERNIST MOVEMENT ON ENGLISH LITERATURE - P. Sujatha (International Journal of Research -GRANTHAALAYAH, 2025)
The Modernist movement, which began towards the late 19th century and continued until the mid-20th century, was a very significant development in English literature. The factors that brought Modernism into human existence-one from industrialization, the other from urbanization, and the third from World War I-liberalized Modernism from Victorian and Romantic traditions, and it became focused on ideas of disillusionment, fragmentation, and alienation in a changed world. It altered narrative techniques, structure, and language, discarding the age-old plot development and linear storytelling. Therefore, this paper delves into the Modernism impact on English literature with the focus on themes such as alienation, identity, time, and social norms. It goes on to show how these authors, including Virginia Woolf, James Joyce, T.S. Eliot, and Ezra Pound, innovatively employed techniques such as stream-of-consciousness, symbolism, and fragmented narratives to portray subjective experiences in a fractured world. These would-be authors created 20th-century literature by their experimentation with form and content, sometimes complexly and ambiguously, to present the realities of modern life. This paper, thus, provides a holistic view of this Modernism legacy in English literature.